Laminated glass beams with thick embedded connections – Numerical analysis of full-scale specimens during cracking regime. (1st July 2018) - Bedon, Chiara; Santarsiero, Manuel
Abstract: Laminated and hybrid glass systems are typically realized by bonding or joining together several structural components and materials. Their structural performance and safe design is hence related to the optimal combination of several parameters, including material properties and degradation, geometrical ratios, connections type and features, etc. This research paper is focused on the numerical assessment of the load bearing performance of full-scale laminated glass (LG) beams with thick embedded connections. There, the structural interaction between multiple glass segments is offered by thick metal inserts, being embedded in the LG sections during the production stage. The overall bending response of such assemblies, given the same glass beam segments, is strictly related to the connection detailing, namely including the number, position, size, etc. of embedded connectors. In this regard, Finite Element numerical models able to properly capture their actual local and global behaviour can represent a robust support for time/cost-consuming full-scale experimental investigations. Refined FE models are hence presented for selected specimen configurations, and validated towards four-point bending experimental tests carried out on LG beams with three different types of embedded connections and available in the literature. In the typical FE model, the geometrical and mechanical properties of the reference specimens are properly taken into account, so to explore both the elastic and post-cracked performance of the LG beams object of study, under specific loading conditions. Comparative results are then critically discussed, giving evidence of major structural performances for the selected configurations, and including a concise parametric study.